Patterns of injuries in homicidal cases - Jain, Sanjay; Patel, Shailendra; Tiwari, Gaurav; Singh, Puja (Saúde Ética & Justiça, 2023)
Death, an inevitable part of life, prompts an exploration into the manner and method by which it occurs. This study aims to analyze the patterns of injuries in homicidal cases brought for postmortem examination. In 2019, a total of 28,918 murder cases were registered in India, showing a slight decrease of 0.3% in comparison to 2018 (29,017 cases). The study aims to understand the different injury patterns in homicide. At the Department of Forensic Medicine, Gandhi Medical College, Bhopal, India, a total of 62 males and 12 females, along with one unknown gender person, where submitted to postmortem examination. The majority of cases belonged to urban, with leading causes of death being shock and hemorrhage followed by craniocerebral damage. This study concludes that sharp edges and deep cuts were the primary injury patterns in homicide cases.